2022
DOI: 10.1002/jev2.12273
|View full text |Cite
|
Sign up to set email alerts
|

A quick pipeline for the isolation of 3D cell culture‐derived extracellular vesicles

Abstract: Recent advances in cell biology research regarding extracellular vesicles have highlighted an increasing demand to obtain 3D cell culture‐derived EVs, because they are considered to more accurately represent EVs obtained in vivo. However, there is still a grave need for efficient and tunable methodologies to isolate EVs from 3D cell cultures. Using nanofibrillar cellulose (NFC) scaffold as a 3D cell culture matrix, we developed a pipeline of two different approaches for EV isolation from cancer spheroids. A ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 61 publications
(76 reference statements)
1
7
0
Order By: Relevance
“…In vitro functional assay 2.12.1 Cells THP-1 cells (ATCC TIB-202), a human monocytic cell line, were grown in complete RPMI media supplemented with 10% EV-depleted fetal bovine serum and 1% GlutaMAX™ Supplement (Gibco). EV depletion from fetal bovine serum was performed using polyethylene glycol 55 . THP-1 cells were plated to 24-well plate at a concentration of 2 x 10 5 viable cells per well and incubated for 48 h in 1 ml/well of media supplemented with 50 nM phorbol 12-myristate 13-acetate (PMA) (Sigma-Aldrich) for differentiation into macrophages.…”
Section: 12mentioning
confidence: 99%
“…In vitro functional assay 2.12.1 Cells THP-1 cells (ATCC TIB-202), a human monocytic cell line, were grown in complete RPMI media supplemented with 10% EV-depleted fetal bovine serum and 1% GlutaMAX™ Supplement (Gibco). EV depletion from fetal bovine serum was performed using polyethylene glycol 55 . THP-1 cells were plated to 24-well plate at a concentration of 2 x 10 5 viable cells per well and incubated for 48 h in 1 ml/well of media supplemented with 50 nM phorbol 12-myristate 13-acetate (PMA) (Sigma-Aldrich) for differentiation into macrophages.…”
Section: 12mentioning
confidence: 99%
“…It should be noted that the various isolation methods of EVs end with different characteristics and potencies in terms of application ( 96 , 97 ). It was shown that EVs from 3D cultures are functionally different and are more similar to the patient-derived EVs compared to those obtained from traditional 2D-culture conditions ( 98 100 ). These imply that spending time for optimization of isolation method/s ( 101 , 102 ) to reach pure EVs with higher efficiency ( 103 ) in a reproducible manner ( 104 ) is of great importance.…”
Section: Extracellular Vesicles a New Therapeutic Paradigm For Autoim...mentioning
confidence: 99%
“…Moreover, classifying EVs according to biogenesis pathways remains difficult, and, for this reason, they have been recommended to be categorized based on physical characteristics, such as size, to “small EVs” (sEVs) and “large EVs” (lEVs) by the MISEV2018 guidelines [ 21 ]. Here, we used two complementary EV methods capable of single EV detection: ( i ) high-sensitive flow cytometry with light scatter calibration based on the Mie theory allowing to accurately size lEVs (200–1000 nm in diameter) [ 22 ] and ( ii ) single particle interferometric reflectance imaging sensor (SP-IRIS) allowing the single detection of sEVs (50–200 nm) [ 23 ].…”
Section: Introductionmentioning
confidence: 99%